2009
DOI: 10.1097/brs.0b013e3181af053c
|View full text |Cite
|
Sign up to set email alerts
|

Teachability and Reliability of a New Classification System for Lower Cervical Spinal Injuries

Abstract: The CSISS is a useful new adjunct in the treatment and classification of lower cervical spine injuries. The system is reliable, reproducible, and teachable. It is clinically useful for all levels of orthopedic training and experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 15 publications
0
7
0
2
Order By: Relevance
“…Using only the spinal injury’s location and true morphological descriptions, excellent agreement ( κ -value: 0.883) and reproducibility ( κ -value: 0.977) can be obtained. Zehnder et al [111] confirmed these findings in an external validation study. One should keep in mind, however, that an excellent reproducibility of a classification system does not say anything about its content and construct validity, nor about its clinical utility.…”
Section: Two Crucial Spinal Injury Characteristics: Location and Morpmentioning
confidence: 57%
“…Using only the spinal injury’s location and true morphological descriptions, excellent agreement ( κ -value: 0.883) and reproducibility ( κ -value: 0.977) can be obtained. Zehnder et al [111] confirmed these findings in an external validation study. One should keep in mind, however, that an excellent reproducibility of a classification system does not say anything about its content and construct validity, nor about its clinical utility.…”
Section: Two Crucial Spinal Injury Characteristics: Location and Morpmentioning
confidence: 57%
“…Another limitation is represented by the difficulties of comparing our data with ICC indicators in other studies. Among present studies that assessed the ICC, 3,4,8 -10 the model and/or form of the ICC are provided in only 2 articles. In one study, authors reported the application of a 2-way random model of the ICC 9 ; however, no data concerning form or the agreement type were provided.…”
Section: Discussionmentioning
confidence: 99%
“…Only 5 published articles have estimated the reliability of the SLIC and CSISS scales, 3,4,8 -10 and only 3 of those were external studies. 8 -10 The CSISS scale has been examined by surgeons with different levels of experience; however, all studies had a single-centre design (Table 1). The SLIC scale has been examined by only experienced surgeons.…”
Section: Introductionmentioning
confidence: 99%
“…Предложенный авторами нестандартный подход к определению степени повреждений, несмотря на допускаемый субъективизм, не приводит к ожидаемо широкому разбросу результатов при проведении контрольных измерений. Так, показатель согласованности при использовании CSISS составляет, по данным разных исследователей, от 0,883 до 0,983, что является очень высоким значением [32,33]. Для сравнения AOSpine subaxial cervical spine injury classification system, снабженная подробными инструкциями и имеющая жесткие критерии оценки, демонстрирует уровень согласованности не более 0,75 [24,34].…”
Section: количественная оценка степени тяжестиunclassified